2022
DOI: 10.1007/s00062-022-01223-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile and Complication Rates in Emergency Off-label Use of Tirofiban in Interventional Neuroradiology

Abstract: Purpose Tirofiban has been approved for the treatment of acute coronary syndrome. Meanwhile, tirofiban is frequently applied in emergency situations in interventional neuroradiology (INR). The objective of this study was to analyze the risk profile for the off-label use of tirofiban in INR patients. Methods Data of 86 patients, who underwent neurointerventional therapy and were treated with tirofiban at 2 neuroendovascular centers between January 2016 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Brockmann et al. analysed the risk profile for the off-label use of tirofiban in interventional neuroradiology patients and concluded that the safety profile of tirofiban, when used off-label in a neuroendovascular setting, is acceptable but noted that the proportionally highest complication risk applies to older patients and patients being treated for acute stroke [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brockmann et al. analysed the risk profile for the off-label use of tirofiban in interventional neuroradiology patients and concluded that the safety profile of tirofiban, when used off-label in a neuroendovascular setting, is acceptable but noted that the proportionally highest complication risk applies to older patients and patients being treated for acute stroke [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that tirofiban is a safe and effective alternative in neuroradiological interventions [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plavix, a thienopyridine derivative, selectively inhibits the adenosine diphosphate (ADP) receptor on platelets and reduces platelet activation and aggregation [ 3 ]. Aggrastat, a glycoprotein IIb/IIIa receptor antagonist, blocks the final common pathway of platelet aggregation by preventing fibrinogen from binding to platelet receptors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their different mechanisms of action, these drugs have distinct pharmacokinetic and pharmacodynamic profiles. Aspirin is rapidly absorbed in the upper gastrointestinal (GI) tract, metabolized by the liver, and excreted by the kidneys [ 4 , 5 ]. Its antiplatelet effect lasts for the lifespan of the platelet, which is about 7-10 days [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation